OBESITY IN THE ASEAN REGION: INDONESIA’S PERSPECTIVE - Suastika, Ketut (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Obesity is a chronic, relapsing, multifactorial, treatable neurobehavioral disease in which an increase in fat mass causes adipose tissue dysfunction and physical fat mass abnormalities cause metabolic, biochemical, and psychosocial health problems. After smoking and armed violence, war, and terrorism, obesity is the third leading cause of social burden. Indonesia, one of the countries with a large population of more than 270 million people, is the world’s fourth most populous country. According to the Ministry of Health of the Republic of Indonesia’s Basic Health Research, the prevalence of obesity in adults increased from 19.1 percent in 2007 to 26.3 percent in 2013 and 35.4 percent in 2018. Obesity is more prevalent in females than in males, at 44.4 percent and 26.6 percent, respectively. As a result, one in every three adults is obese. Overweight and obesity were prevalent in children at a rate of 20%, or one in every five children. According to the World Obesity Atlas (2022), Indonesia has 14 million females (14%) and 8 million males (8%) who are obese (BMI >30 kg/m2) The situation is a health burden as well as a financial burden for individuals and the state. The potential impact of rising obesity rates is an increase in the prevalence of prediabetes (IGT) and diabetes in Indonesia, which were 10.2 percent and 5.7 percent in 2007, 29.9 percent and 6.9 percent in 2013, and 30.8 percent and 10.9 percent in 2018. According to the 2019 IDF Atlas, Indonesia has the world’s third largest adult population with prediabetes, with 29.1 million people and more recently, according to the 2021 IDF Atlas, Indonesia has the world’s fifth largest population of adults with diabetes, with 19.5 million people. Overweight and obesity also contribute to the prevalence of diabetes, hypertension, and ischemic heart disease, which are 5,020,2 thousand, 11,147.5 thousand, and 282.7 thousand, respectively. Another burden is the loss of 6-10 productive years. This consumes about 8% to 16% of national healthcare, and the total cost (direct and indirect) for obesity in 2016 is USD 2-4 billion. CONCLUSION The Indonesian government is well aware of the situation and has made obesity and prediabetes prevention a priority. Obesity and prediabetes prevention and intervention programs have been developed by the Ministry of Health in collaboration with professional associations.